ẢNH HƯỞNG CỦA HỢP CHẤT HỮU CƠ LÊN QUÁ TRÌNH SINH TRƯỞNG VÀ PHÁT TRIỂN CỦA CHỒI LAN VÂN HÀI (PAPHIOPEDILUM CALLOSUM) NUÔI CẤY IN VITRO - Tán Nhựt, Dương (Vietnam Journal of Science and Technology, 2014)
In the present study, in vitro Paphiopedilum callosum shoots cultured at Department of Plant Molecular Biology and Plant Breeding Biology (Tay Nguyen Institute of Biology) were used as source material. P. Callosum shoots with three 2-cm long leaves were cultured on media supplemented with different organic additives in order to find out the most suitable extract for shoot growth and development, to obtain healthy plantlet and to decrease consumer price of seedlings. The supplementation of young coconut water, rice water, potato starch, banana extract and peptone were investigated. Results showed that kind of organic additive had a great influence on the shoot growth and development. Media supplemented with 20% (v/v) rice water resulted in the best growth and development after 90 days of culture. Moreover, these organic additives used as replacements to young coconut water should be applied to reduce costs for media preparation and price of seedlings while vigorous P. Callosum shoot growth and development is achieved.